VAT and the FDRE Constitution: Is VAT Really an Undesignated Tax? - Silesh, Gizachew Chanie (Bahir Dar University Journal of Law, 2022)
There has been a growing interest in the application of value added tax (VAT) on a global level. Yet the adaptability of VAT in federal systems has come to be a subject of discourse and experimentation in several countries. Ethiopia introduced VAT in 2002, and thereby, as federal state, faced issues of how best to design VAT in a federal set up. The introduction of VAT in Ethiopia was allegedly justified under the constitutional clause of â€œundesignated powers of taxation.â€ Though it was said to be undesignated tax power, practically speaking it has brought changes in the already existing distribution power of taxation by shifting part of statesâ€™ power of taxation over sales tax to the federal government. This article explores how VAT is adapted in the Ethiopian case both from practical and constitutional perspectives. It begins by reviewing the salient features of the constitutional provisions on tax allocation and description of the actual division of power of taxation between federal government and the states in Ethiopia, and then proceeds to the survey of the features of the VAT introduced in Ethiopia. The main focus is to explore the question of whether or not VAT was designated in the FDRE Constitution. In other words, it enquires into the issue of whether the introduction of VAT as undesignated tax power is in line with the constitution or not? After due analysis, the author concludes that the Ethiopian VAT legislation is not in congruity with the FDRE Constitution.